The Effect of Hero Archetype in Advertising on Perceived Product Efficacy - Laksmidewi, Dwinita; Susianto, Harry; Afiff, Adi Zakaria (Indian Journal of Marketing, 2017)
This study aimed to examine the effect of the hero archetype in advertising on perceived product efficacy and purchase intention. The hero character was tough and brave to overcome a great trial; he was fighting to achieve a noble goal, and successfully demonstrated the pride’s superiority. The use of archetype in advertising attempts to convey meaning to products ; the universal archetype characters can help tell the story of a brand in an easier way. The results of this study suggested that the use of hero archetype in an ad can trigger anthropomorphism, and had a positive effect on perceived product efficacy and purchase intention. Further, the results indicated that the warrior character in a hero had positive effects on perceived product efficacy for male consumers and for consumers with less power.